FROM THE EXPERIENCE OF TEACHER CERTIFICATION IN FOREIGN COUNTRIES - Elina N. Yakovleva; Irina Y. Krasilova (Russian State Vocational Pedagogical University, 2015)
The purpose of the article is to review foreign experience of teacher certification according to requirements of the Teacher Professional Standards.Methods. The authors use analysis and generalization of official documents and methodical recommendations of the European Commission on introduction of a system of professional competences (standards) of the teacher; guides for certification of teachers in the EU countries, the USA and Australia according to standards of the teacher; regulations of Russian centers for certification of pedagogical workers using in their activities overseas experience of similar centers and the international standard of personnel certification.Results. Various options for the use of a system of the teacher professional competencies (standards), as well as models of independent certification of teachers in terms of approaches, goals, objectives and organizational forms used in the EU, the USA and Australia are considered and analysed.Scientific novelty. As a result of the analysis of teacher certification experience in a number of foreign countries some general tendencies are identified and taken into account in the recommendations on the establishment of the system of Russian teachers certification as consistent with the Professional Standard «Teacher (pedagogical activity in the field of pre-school, primary general, basic general, secondary general education) (educator, teacher)».Practical significance. The results can be used while developing of regional centres for teachers' independent certification.